Microbiological Features of Solid State Fermentation and its Applications - An overview - Mienda, Bashir Sajo; Idi, Ahmad; Umar, Abdulhamid (Research in Biotechnology, 2011)
Solid state fermentation [SSF] has been recently considered as the most cheapest and more environmentally friendly relative to submerged liquid fermentation [SLF] in the production of value added industrial based products such as enzymes, bio fuels and the likes. The merit and demerit of SSF and SLF has been summarized. The main microorganisms that occupied a pivotal position in achieving absolute SSF processes have been highlighted. A typical process and production characteristic of a selected bioreactor has been addressed within the concept of SSF. The applications of the process in various economic sectors such as industrial fermentation, agro food industry and environmental control have been reported. This review aimed at gathering the disperse literature on the current state of art on SSF, its advantages and disadvantages relative to SLF and their various applications.